Factors Negatively Affecting the Development of The Agricultural Economy of Our Country (International Journal of Scientific Trends, 2023)
Agricultural economy maximally satisfies the demand for food security of countries. There is a sector with a developed economy, which shows an increase in the income of the population and the development of the country. If there are factors that have a negative impact on this, it is the need of the hour to eliminate them by developing strategic projects.